Beyond the sling : a real-life guide to raising confident, loving children the attachment parenting way - Bialik, Mayim (Simon & Schuster, 2012)
The author describes how she forged positive relationships with her sons through Attachment Parenting practices, sharing advice on how to address a child's needs without resorting to pop culture trends.